Auction Theory from an All-Pay View: Buying Binary Lotteries - Wolfgang Leininger (Center for Economic Studies and ifo Institute (CESifo), 2000)
An auction is viewed as a process that in equilibrium generates a binary lottery for each bidder, which the bidder buys with his bid. This view allows for a simple way to consistently assess differences in bidding behavior over different bidders and different auctions. E.g. all auctions covered by the Revenue Equivalence Theorem are shown to generate lotteries with identical probabilities, but different pay-offs. It is then argued, that understanding of (experimentally observed) bidding behavior in auctions is enhanced by drawing on the large literature on choice behavior over lotteries.
Keywords: 330